NYE STYRINGSREDSKABER I SOCIALT ARBEJDE: Arbejdsevnemetoden som et lovmæssigt imperativ - Hammen, Ida (Tidsskriftet Antropologi, 2008)
This article shows how the view of the citizen as a rational actor has become an infl uential perspective in Danish social work. The perspective is represented both by numerous researchers and leading politicians in Denmark. Politically, the introduction of a new social work method, the “arbejdsevnemetode” (the ability to work method), is an example of how the perspective is implemented in practice. The method aims to cast the citizen as a competent, rational actor, and the method’s use is mandatory in cases concerning early retirement, rehabilitation, and fl ex- time jobs. The rational actor perspective is also supported by a prominent group of social researchers who wish to challenge clientization in Danish social work. Based on data from a fi eldwork conducted in three Danish public administrations, the article explores the effects of the rational actor perspective on everyday municipal practice, as it is implemented via the “arbejdsevnemetode”. Furthermore it analyses the representation of the discourse from the infl uential research group on the social fi eld. The main concern of the article is not so much to argue for or against the rational actor perspective, but rather to analyse how ideological changes occur in different areas of social work. It concludes that it is the rigorous implementation of the rational actor perspective, rather than its intent that leads to problems in both practical and scientific settings.